274 Low-Grade Carcinoma Ex-Pleomorphic Adenoma: Diagnostic Challenges Caused by Fine Needle Aspiration. (11th January 2018) - Ambelil, Manju; Compton, Frances; Covinsky, Michael; Zhu, Hui
Abstract: Objectives: Fine needle aspiration (FNA) is a cost-effective and rapid method to diagnose salivary gland neoplasms. Histological changes secondary to FNA are usually mild and focal, with only rare cases of complete tumor necrosis reported. We report a case of a low-grade carcinoma ex-pleomorphic adenoma (CXPA) with diffuse post FNA reactive changes. Low-grade CXPA is a rare malignancy that can be difficult to diagnose; the post FNA changes makes the diagnosis even more challenging. Methods: The patient was a 46-year-old man with a right parotid mass of 3 years' duration. CT scan showed a well-circumscribed 3.9 cm mass in the superficial lobe. FNA demonstrated cytomorphologic features typical for pleomorphic adenoma, with ductal epithelium, myoepithelial cells, and chondromyxoid stroma. Subsequently he underwent right parotidectomy eight days after FNA. Results: Gross examination showed a 5.5 cm well-circumscribed mass with heterogeneous cut surface. Microscopically, tumor composed of cells forming ducts with islands of squamous differentiation and focal chondromyxoid stroma. Necrotic areas associated with focal atypia and increased mitosis was present. Capsule showed diffuse edema, lymphocytic infiltrates, and extensive fibroblastic proliferation. Surrounding salivary gland tissue demonstrated diffuse acinar atrophy and ductal proliferation. Careful inspection of capsule showed several foci with extension of tumor beyond fibrous capsule, invading into normal salivary glands. The area of extension beyond capsule measured <1.5 mm in largest focus. Diffuse reactive/reparative changes made the assessment and measurement of invasion difficult. After multiple intra- and inter-departmental discussions, a diagnosis of low-grade salivary mixed neoplasm consistent with CXPA minimally invasive was made. Conclusion: In our case, diffuse reactive changes secondary to prior FNA made the diagnosis difficult. The short interval between FNA and surgery might explain these changes. We propose that a longer interval between FNA and surgery is more appropriate to prevent false positive/negative diagnosis as a result of reactive changes.